The Role of Family Law in Preventing Problematic Polygamy and Protecting Children's Rights in Indonesia - Nida Roudhotul Hikmah (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The issue of polygamy in Indonesia remains a sensitive matter that often causes legal, social, and psychological problems, especially when the practice is carried out without fulfilling the principles of justice and legal procedures. The impact not only causes vulnerability for wives, but also threatens the fulfillment of children's rights, such as the right to identity, education, and protection from discrimination. This study aims to analyze the role of family law in preventing problematic polygamy while strengthening the protection of children's rights in Indonesia. The research method used is normative legal research with a legislative and conceptual approach, supplemented by an analysis of religious court practices. The results show that family law plays an important role in preventing problematic polygamy for the sake of justice and welfare. Polygamy is permitted in Islam on the condition of fairness, but in practice it often harms women and children. Family law serves to regulate and protect vulnerable parties in the family for the sake of child-oriented social justice. Furthermore, family law in Indonesia plays an important role in protecting children's rights from the effects of problematic polygamy, divorce, and parental neglect. Protection is provided through the strengthening of marriage and birth registration regulations, the optimization of the role of religious courts by considering the interests of children, and the digitization of legal services to facilitate access and prevent unregistered marriages.